The Prevalence, Predictors, and In-Hospital Mortality of Hepatic Encephalopathy in Patients with Liver Cirrhosis Admitted at St. Dominic Hospital in Akwatia, Ghana - Duah, Amoako (Can J Gastroenterol Hepatol, 2020)
BACKGROUND: Hepatic encephalopathy (HE) is one of the most debilitating complications of cirrhosis leading to death. Decrease in HE mortality and recurrence has been linked with timely identification and early treatment. There is a need to document the burden, predictors, and treatment outcomes of HE in an adult population with liver cirrhosis in our setting as only reports from resource-endowed countries abound in the literature. This study aimed therefore to determine the prevalence, predictors, and treatment outcomes of patients with liver cirrhosis admitted at St. Dominic Hospital (SDH) in Akwatia, Ghana. MATERIALS AND METHODS: A prospective study was conducted involving one hundred and sixty-seven (167) patients admitted at the medical wards in SDH with liver cirrhosis from January 1st, 2018, to March 24th, 2020. The demographic and clinical features of the patients were collected using a standardized questionnaire. Biochemical, haematological, and abdominal ultrasound scans were done for all patients. Patients were then followed up until discharge or death. RESULTS: There were 109 (65.3%) males out of the 167 patients with a mean age of 45.8 and 47.5 years for those with and without HE, respectively. The prevalence of HE was 31.7% (53/167). Out of 53 participants with HE, 75.5% (40/53) died. There was a strong association between HE and death (p < 0.001). The major precipitating factor of HE was infection (64.2%). Severe ascites (OR = 0.009) were clinical feature independently associated with HE, whereas high creatinine (OR = 0.987), blood urea nitrogen (BUN) (OR = 1.199), Child–Pugh score (CPS) (OR = 5.899), and low platelets (OR = 0.992) were the laboratory parameters and scores independently predictive of HE. CONCLUSION: HE was common among patients with liver cirrhosis admitted at SDH with high in-patient mortality. The commonest precipitating factor for HE was infection(s). Severe ascites, low platelet count, high creatinine, BUN, and CPS were independent predictors of HE.